LANGUAGE TEACHING AND EVALUATION: AN ANALYSIS ON STUDENTS’SPEAKING PERFORMANCE ASSESSMENT - Putri Novitasari (LPPM Universitas Kahuripan Kediri, 2021)
Abstract Assessment in classroom activities can be derived by using various sources, within oral or written. Related to the assessing students’ performance, this study willdiscuss on the assessment of students’ speaking performance. The data collected by giving questionnaire to the three different English Department lecturers from three different private universities. The questionnaire consists of eight points which is used to get the information related to speaking assesment. The items of question are; 1) the criteria of a good speaking performance, 2) the way of developing scoring rubric, 3) the common errors of learners, 4) The common activities in speaking performance, 5) the ice breaking activity, 6) the most contributed activity of learners’ score, 7) the percentage of final test score, and 8) the problem in assessing speaking performance. A descriptive qualitative design was use to conduct this research. The research results reveal two points which are in lining among three lecturers. First is the scoring system. Generally among three lecturers use certain number criteria for scoring learners’ speaking performance. Each lecturer use their own scale criteria but, actually they use same method, maximal and minimal scales. The second similarity is among three lecturers actually have same argument or maybe that problem is generally happened in assessing speaking performance. The problem is time consuming while assessing learners’ presentation, speech, or debate. Finally, more specific focus on extensive speaking performance assessment may give broader finding and detail information. Keywords : evaluation, assessment, speaking. Abstrak: Assesmen dalam kegiatan belajar mengajar dapat dilakukan dengan berbagai cara, baik lisan atau tertulis. Sehubungan dengan assesmen yang dilakukan padapenampilan siswa, penelitian ini akan membahas tentang assesmen pada kemampuan speaking siswa. Data pada penelitian didapatkan dengan metode kuisioner yang diberikan kepada 3 orang tenaga pengajar yang berasal dari 3 universitas swasta yang berbeda. Kuisioner terdiri dari 8 item, yang berisi antaralain; (1) kriteria kemampuan speaking yang bagus; (2) rubrik penilaian; (3) kesalahan yang umum dilakukan siswa; (4) kegiatan pembelajaran dalam speaking;(5) kegiatan pembuka; (6) kegiatan yang berpengaruh banyak pada nilai siswa; (7) persentase nilai akhir siswa; (8) kendala dalam proses assesmen. Hasil daripenelitian ini memunculkan dua simpulan yang didapat dari hasil kuisioner yang dilaksanakan. Hasil tersebut pertama dari penyusunan rubrik penilaian spaking, dari ketiga narasumber masing-masing menggunakan rentang nilai tersendiri tetapi mtode penilaian yang mereka gunakan sama yaitu menggunakan standar nilai tertinggi dan terendah. Kedua, kendala dalam proses assesmen, ketiga narasumber mengungkapkan bahwa kendala yang muncul adalah waktu terutama pada kegiatan presentasi, pidato, dan debat. Kata kunci: assesmen, speaking